PENGARUH VIDEO TUTORIAL TERHADAP KETERAMPILAN PEMELIHARAAN MESIN SEPEDA MOTOR DI SMK MUHAMMADIYAH BAWANG - Budiyanto; Burhan , Nurul (Journal of Automotive Technology Vocational Education, 2024)
This study aims to determine: The Effect of Video Tutorials on Motorcycle Engine Maintenance Skills of Class X Students at SMK Muhammadiyah Bawang. This study uses a Quasi Experimental Design research method with a nonequivalent control group design approach. The subjects of this study were 50 class X students of Motorcycle Engineering and Business Expertise Competence at SMK Muhammadiyah Bawang. Data collection used a practice assessment sheet. The data analysis technique used descriptive analysis by calculating the mean (Me), median (Md), mode (Mo), standard deviation and percentage. The data collection technique used pretest and post-test. The results showed that before being given treatment, the control group and the experimental group showed a lack of skills in motorcycle maintenance. However, after being given treatment, both groups showed an increase in skills in motorcycle maintenance. The increase was reviewed from the comparison of post-test values. In the control group, the increase occurred by 12% while the experimental group increased by 28.95%. After the application of learning with video tutorials and conventional learning, there was a difference in values ​​with a percentage of 3.5%. This shows that video tutorials influence motorcycle engine maintenance skills. Keywords: Video Tutorials, Skills, Motorcycle Engine Maintenance.